Identification and Classification of Prescription Errors at a Tertiary Hospital in Southeast Nigeria - Patricia Uche Ogbo; Chioma Assumpta Okonkwo; Collins Chukwuemeka Magbo; Chidimma Maryrose Ononugbo; Cyndi Chinelo Ofolebe; Nathaniel Chinonso Okafor; Charles Chiemela Nwaobilor; Ogochukwu Ifeoma Ugwuede; Chimezie William Nnaji (Ibom Medical Journal, 2025)
Background: Prescription errors are the most common type of medication errors that occur in healthcare settings, and they are risk factors to adverse effects, drug therapy problems and failure in therapeutic goals.